Second Primary Cancers After Gastric Cancer, and Gastric Cancer as Second Primary Cancer - Zheng, Guoqiao (Clin Epidemiol, 2021)
BACKGROUND: Second primary cancers (SPCs) are increasing, which may negatively influence patient survival. Gastric cancer (GC) has poor survival and when it is diagnosed as SPC it is often the cause of death. We wanted to analyze the risk of SPCs after GC and the risk of GC as SPC after any cancer. Such bidirectional analysis is important in relation to fatal cancers because SPCs may be under-reported in the short-term survival period. METHODS: Cancers were obtained from the Swedish Cancer Registry from years 1990 through 2015. Standardized incidence ratios (SIRs) were used to estimate bidirectional relative. RESULTS: We identified 23,137 GC patients who developed 1042 SPCs (4.5%); 2158 patients had GC as SPC. While the risk for three SPCs was increased after GC, seven first primary cancers were followed by an increased risk of GC as SPC, including esophageal, colorectal, bladder, squamous cell skin and breast cancers and non-Hodgkin lymphoma. Breast cancer, which was followed by a diagnosis of second GC, showed an excess of lobular histology. CONCLUSION: Multiple primary cancers in the same individuals may signal genetic predisposition. Accordingly, the association of GC with breast cancer may be related to mutations in the CDH1 gene, and clustering of colorectal, small intestinal and bladder cancers could be related to Lynch syndrome. The third line of findings supports a contribution of immune dysfunction on the increased risk of GC as SPC after skin cancer and non-Hodgkin lymphoma. Early detection of GC in the risk groups could save lives.